John Bellairs' Johnny Dixon in The bell, the book, and the spellbinder - Strickland, Brad.; Bellairs, John. (New York : Dial Books for Young Readers, 1997)
When Fergie falls under the spell of an evil sorcerer, Johnny Dixon and Professor Childermass risk their own lives to save him.
Based on the characters of John Bellairs.
Keywords: Magic -- Fiction; Wizards -- Fiction